Regional protection scheme for distribution network based on logical information. Issue 17 (2nd October 2017) - Ma, Jing; Xiang, Xiaoqiang; Zhang, Runfeng; Li, Pei; Liu, Jing; Thorp, James S.
Abstract : In view of the incorrect operation of local protection caused by multiple distributed generations (DGs) and branches in distribution system, a regional protection scheme for distribution network based on logical information is proposed here. Moreover, a regional centralised protection system in parallel with and independent from the existing protection system is constructed. First, the problems in local current protection of lines with multiple DGs and branches are analysed. On this basis, protection regionalisation is conducted according to the configuration of circuit breakers. Also then, by combining the start‐up information of existing over‐current protection set‐I, set‐II, and set‐III, the operation criterion of regional protection is formed. Simulation tests on the IEEE 33‐node distribution system verify that, the proposed scheme could accurately locate in‐zone fault and block out‐of‐zone fault, accelerate protection operation, and shorten the outage time. Besides, the proposed criterion is fault tolerant due to redundancy in the multi‐source information used. With small amount of information transmission, the requirement on information synchronisation is low.